Impac Activity Dhikir Terhadap Kecerdasan Spiritual Siswa Di Madrasah Aliyah Al-Muawanah Minggir Candi Sidoarjo - Siti Maimunah; Rusdianingseh Rusdianingseh; M. Shodiq; Nunik Purwanti (Departement of Mathematics Education, 2023)
This research is motivated by the behavior of the students of Madrasah Aliyah, the condition is because the ethics of the children are not in accordance with what is taught in Islamic education at school and the level of SQ is low. Students of Madrasah Aliyah Al-Muawanah Minggir Sidoarjo are aged 15 to 17 years who are included in the category of teenagers. At this time children are now vulnerable to being influenced by the environment, technological and cultural developments that can trigger teenagers to behave deviantly.The effect is that teenagers when studying at school lack discipline, one of which is truancy. being late for school, fighting, untidy clothes, vandalism, garbage problems. To prevent student deviation, it is necessary to have activities to improve ESQ with istighosah.This study aims to find out and examine the dzikir activities on the spiritual intelligence of the students of Madrasah Aliyah Al-Muawanah Minggir Sidoarjo.This research includes comparative research, namely research that compares the existence of one or more variables in two or more variables or different samples or time, the type of data in this study is quantitative, and the measurement scale uses a Likert scale, the paradigm in this study is simple where this study consists of two dependent variable and two independent variables so to compare between the Independent Test Test technique used.The research subjects were 22% of the total 120 students of Madrasah Aliyah Al- Muawanah Minggir Sidoarjo. Data collection techniques using questionnaires, observations, interviews and documentation. While the data analysis technique used is the Independent Test Test in consultation with the r table at a significant level of 5% and 1% to provide an interpretation that the alternative hypothesis is accepted or rejected. The results of this study indicate that there is a positive and significant effectiveness of istighosah activities on the spiritual intelligence of students of Madrasah Aliyah Al- Muawanah Minggir Sidoarjo.